STXBP2-R190C Variant in a Patient With Neonatal Hemophagocytic Lymphohistiocytosis (HLH) and G6PD Deficiency Reveals a Critical Role of STXBP2 Domain 2 on Granule Exocytosis - Benavides, Nathalia; Spessott, Waldo A.; Sanmillan, Maria L.; Vargas, Marcelo; Livingston, Mylynda S.; Erickson, Nissa; Pozos, Tamara C.; McCormick, Margaret E.; Scharrig, Emilia; Messinger, Yoav H.; Giraudo, Claudio G. (Frontiers in Immunology, 2020)
Neonatal hemophagocytic lymphohistiocytosis (HLH) is a medical emergency that can be associated with significant morbidity and mortality. Often these patients present with familial HLH (f-HLH) which is caused by gene mutations interfering with the cytolytic pathway of Cytotoxic T-lymphocytes (CTLs) and Natural Killer (NK) cells. Here we describe a male newborn who met HLH-diagnostic criteria, presented with profound cholestasis and carried a maternally inherited heterozygous mutation in Syntaxin-Binding Protein-2 [STXBP2, c.568C>T (p.Arg190Cys)] in addition to a severe pathogenic variant in Glucose 6-Phosphate Dehydrogenase [G6PD, Hemizygous c.1153T>C (Cys385Arg)]. Although mutations in STXBP2 gene are associated with f-HLH type 5, the clinical and biological relevance of the p.Arg190Cys mutation identified in this patient was uncertain. To assess its role in disease pathogenesis, we performed functional assays and biochemical and microscopic studies. We found that p.Arg190Cys mutation did not alter the expression or subcellular localization of STXBP2 or STX11, neither impaired the STXBP2/STX11 interaction. In contrast, forced expression of the mutated protein into normal CTLs strongly inhibited degranulation and reduced the cytolytic activity out-competing the effect of endogenous wild-type STXBP2. Interestingly, Arginine 190 is located in a structurally conserved region of STXBP2 where other f-HLH-5 mutations have been identified. Collectively, data strongly suggest that STXBP2-R190C is a deleterious variant that acts in a dominant-negative manner by probably stabilizing non-productive interactions between STXBP2/STX11 complex and other still unknown factors such as the membrane surface or Munc13-4 protein and thus impairing the release of cytolytic granules. In addition to the contribution of STXBP2-R190C to f-HLH, the accompanied G6PD mutation may have compounded the clinical symptoms; however the extent by which G6PD deficiency has contributed to HLH in our patient remains unclear